2021
DOI: 10.1038/s41396-021-00922-0
|View full text |Cite
|
Sign up to set email alerts
|

Climate change alters temporal dynamics of alpine soil microbial functioning and biogeochemical cycling via earlier snowmelt

Abstract: Soil microbial communities regulate global biogeochemical cycles and respond rapidly to changing environmental conditions. However, understanding how soil microbial communities respond to climate change, and how this influences biogeochemical cycles, remains a major challenge. This is especially pertinent in alpine regions where climate change is taking place at double the rate of the global average, with large reductions in snow cover and earlier spring snowmelt expected as a consequence. Here, we show that s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
50
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(54 citation statements)
references
References 66 publications
(77 reference statements)
4
50
0
Order By: Relevance
“…Our results suggest that different afforested plantations changed ecosystem functioning seasonally, consistent with previous nding [60]. We found a positive relationship between microbial diversity and composition and multifunctionality in plantation forests seasonally, corroborating the positive biodiversity-ecosystem function relationships.…”
Section: Diversity-function-assembly Relationship With Seasonalitysupporting
confidence: 92%
See 1 more Smart Citation
“…Our results suggest that different afforested plantations changed ecosystem functioning seasonally, consistent with previous nding [60]. We found a positive relationship between microbial diversity and composition and multifunctionality in plantation forests seasonally, corroborating the positive biodiversity-ecosystem function relationships.…”
Section: Diversity-function-assembly Relationship With Seasonalitysupporting
confidence: 92%
“…A similar nding showed that oxidative activities were more variable than hydrolytic activities and increased with soil pH [59]. In addition, as mentioned previously, microbes typically invest more in enzymes, especially lignin-degrading enzymes, in summer [60]. In contrast, potential enzyme activities were potentially expected to be high in winter.…”
Section: Effect Of Seasonality On Soil Enzymessupporting
confidence: 60%
“…Root N is subsequently translocated to aboveground biomass (De Vries, Bloem, et al., 2012; Harrison et al., 2007), and eventually transferred to soil organic matter pools via shoot, root, and microbial turnover (Zogg et al., 2000). However, N turnover and uptake dynamics in mountain ecosystems vary strongly over the growing season (Broadbent et al., 2021), with plant and microbial uptake and competition increasing towards peak biomass (Bardgett et al., 2002). Thus, our findings from the late growing season may not reflect ecosystem N uptake and retention in the early growing season.…”
Section: Discussionmentioning
confidence: 99%
“…We listed Betaproteobacteria here separately, as Kaiju assign them separately and does not have the SILVA132 database assignment. In the paper, Beta - and Gammaproteobacteria are summed ( 92 , 93 ). Download .…”
Section: Resultsmentioning
confidence: 99%